2011
DOI: 10.2528/pier10120702
|View full text |Cite
|
Sign up to set email alerts
|

Depolarization of Metric Radio Signals and the Spatial Spectrum of Scattered Radiation by Magnetized Turbulent Plasma Slab

Abstract: Abstract-The mutual correlation function of the phase fluctuations of scattered ordinary and extraordinary waves by the magnetized plasma slab with electron density fluctuations and the variance of the Faraday angle is calculated by the perturbation method. Analytical expression of broadening of the spatial spectrum of scattered radiation is obtained for arbitrary fluctuation spectrum. Numerical calculations are carried out for the anisotropic Gaussian fluctuation spectrum at different anisotropy factor and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…plasma thickness with different N e0 calculated using (23) and (24 (24)). It is shown in Figure 4 that the variance of plasma frequency with the radial distance becomes faster as N e0 is bigger.…”
Section: Propagation and Polarization Characteristics Affected By Elementioning
confidence: 99%
See 2 more Smart Citations
“…plasma thickness with different N e0 calculated using (23) and (24 (24)). It is shown in Figure 4 that the variance of plasma frequency with the radial distance becomes faster as N e0 is bigger.…”
Section: Propagation and Polarization Characteristics Affected By Elementioning
confidence: 99%
“…In fact, some phenomena such as Faraday-rotation or dual-refraction will occur when EM wave propagates in magnetized plasma [22][23][24], which means magnetized plasma can evidently change the EM wave polarization. Polarization characteristics of scattered EM signals provide important information about physical conditions in the area of localization of the sources and about the medium parameters on the path of wave propagation, so the analysis of the variance of polarization characteristics of EM waves that pass through a magnetized plasma slab is very important in many practical applications such as communication through the plasma sheath and plasma stealth [22][23][24][25]. The transformation of EM wave polarization under reflection from thin solid-plasma film on the conditions of plasma resonance was investigated by Bakunov and Zhukov [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these works, the depolarisation effect is not taken into account and has not been studied in detail, even though it has been shown that the magnetic shear in a tokamak plays no role (Mazzucato 1998). This phenomenon is known in other domains of telecommunication (Tenouxa & Lostanlen 2012), space plasma Physics (Jandieri et al 2011) or laser plasma Physics (Javan & Adli 2013), and only recently in fusion in (Mirnov et al 2014). The polarisation changes have been studied in Astrophysics (Ledenev et al 2002).…”
Section: Contextmentioning
confidence: 99%
“…These lines result from the transition of 3 P 3/2 state to 3 S 1/2 state at 409.99 nm and 5 P 3/2 state to 3 S 3/2 state at 390.01 nm. The intensity of N-I spectral lines was obtained from the spectrum by integrating over line profile and normalizing with the spectral response of the instrument [15]. The E, g and A for selected lines can be taken from the NIST Atomic Spectra Datasheet [16].…”
Section: Optical Emission Spectroscopymentioning
confidence: 99%